MAGNETIC-PROPERTIES BEHAVIORS IN FE88ZR7B4CU1 NANOCRYSTALLINE ALLOY PREPARED BY DIFFERENT POSTANNEAL COOLING RATES - KIM, KY; LEE, JS; NOH, TH; KANG, IK; KANG, T (AMER INST PHYSICS, 1994)
Effects of cooling rate after annealing on the soft magnetic properties were investigated for an Fe88Zr7B4Cu1 alloy with nanoscale grain structure, which was prepared by melt quenching. As the cooling rate increased, the effective permeability improved and the remanence ratio, which indicates the orientation of magnetic anisotropy (degree of pair ordering), decreased. The increase of permeability and decrease of remanence ratio were considered to result from the suppression of the induced magnetic anisotropy. Furthermore, the variation of disaccommodation behaviors with cooling rate was investigated in the Fe88Zr7B4Cu1 nanocrystalline alloy. It was found that the value of D (intensity of disaccommodation) was a little higher for the samples obtained from the high cooling rate than that for the low cooling rate. This result can be explained by domain structure stabilization due to local induced magnetic anisotropy.